Coexistence of SMA Type I with Citrate Transporter Deficiency Disorder: A Case Report - Tawari, Asmaa Al; Pavlovic, Milen; Heberle, Lada Cindro; Bastaki, Laila (Journal of Pediatric Epilepsy, 2024)
The coexistence of spinal muscular atrophy (SMA) with other diseases has been rarely described. We report a unique case with dual pathogenic gene mutations: survival motor neuron 1 (SMN1) gene causing SMA and SLC13A5 gene causing citrate transporter deficiency-induced epilepsy (early infantile epileptic encephalopathy 25, OMIM 615905).A girl presented with recurrent focal seizures with semiology of eyelid blinking, deviation of eyes, and facial twitches, which started on the second day of her life. Interictal EEG showed bilateral multifocal and generalized discharges. Brain MRI revealed delayed myelination and generalized volume loss. PET scan showed diffuse cortical hypometabolism. She had refractory seizures, including two episodes of status epilepticus while being treated with various antiseizure medications. Genetic analysis revealed a homozygous deletion of the SLC13A5 gene at 17p13.1. At 1 year of age, progressive hypotonia, initially ascribed to seizures and antiseizure medications, the appearance of tongue fasciculations and the need for respiratory support, prompted testing for SMA. Mutation at the SMN1 gene locus (5q11.2-13.2) was found and an SMA type I diagnosis was established. EMG/nerve conduction velocity revealed a motor neuron disorder. She was started on nusinersen at the age of 2.5 years once it became available. She was tracheostomized for bilevel positive airway pressure support. At the age of 4.5 years, she had a cardiac arrest and passed away.This is a case report of coexistent mutations in the SMN1 and SCL13A5 genes with overlapping and diagnostically confusing features of progressive hypotonia. The constellation of these separate genetic entities constitutes a clinical phenotype that has not been reported previously.
Keywords: citrate transporter deficiency; spinal muscular atrophy